Tetraphenylethene–pyridine salts as the first self-assembling chemosensor for pyrophosphate1. Issue 12 (21st June 2015) - Xu, Hao-Ran; Li, Kun; Jiao, Shu-Yan; Pan, Sheng-Lin; Zeng, Jun-Ru; Yu, Xiao-Qi
<x xml:space="preserve">Abstract</x> Tetraphenylethene–pyridine salts could self-assemble with PPi into nanoparticles in aqueous solution with color change as well as fluorescence intensity enhancement, which could serve as a novel approach for pyrophosphate sensing.